2021
DOI: 10.1186/s13054-020-03447-8
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and reliability of actigraphy to monitor sleep in intensive care patients: an observational study

Abstract: Background Sleep amongst intensive care patients is reduced and highly fragmented which may adversely impact on recovery. The current challenge for Intensive Care clinicians is identifying feasible and accurate assessments of sleep that can be widely implemented. The objective of this study was to investigate the feasibility and reliability of a minimally invasive sleep monitoring technique compared to the gold standard, polysomnography, for sleep monitoring. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In subsequent studies, this analysis may be extended to cytologies and autopsies to reduce their waiting times. The results can be extrapolated to other health services ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, this analysis may be extended to cytologies and autopsies to reduce their waiting times. The results can be extrapolated to other health services ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed associations between sleep characteristics and relevant health outcomes for ICU patients (delirium, length of ICU stay, length of mechanical ventilation, complications during ICU stay, and mortality). Whether tools were validated or not in the ICU population was based on the Clinical Practice Guidelines for the Prevention and Management of Pain, Agitation/Sedation, Delirium, Immobility, and Sleep Disruption in Adult Patients in the ICU (PADIS) [1], the American Academy of Sleep Medicine [22], and a more recent study on actigraphy [154].…”
Section: Main Outcomesmentioning
confidence: 99%
“…It has been used to track circadian rest-activity cycles and to identify states of wakefulness and sleep [1]. A more recent study has found that ACTG have a moderate level of agreement with PSG in distinguishing between sleep and wakeful states which is more profound in non-ventilated patients [2]. Moreover, ACTG provides an objective physiological assessment via non-invasive use of motion accelerometers to detect multiplanar gross motor activity [2], indicating purposeful or nonpurposeful movement of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study has found that ACTG have a moderate level of agreement with PSG in distinguishing between sleep and wakeful states which is more profound in non-ventilated patients [2]. Moreover, ACTG provides an objective physiological assessment via non-invasive use of motion accelerometers to detect multiplanar gross motor activity [2], indicating purposeful or nonpurposeful movement of patients. Especially, non parametric values (IS: intradaily stability; IV: interdaily variability; L5: least active 5-hour period; M10: most active 10-hour period; and RA: relative amplitude) can quantify circadian rest-activity rhythm providing an indication of circadian rhythmicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation